What would households pay for a reduction of automobile traffic? Evidence from nine German cities - Nicolas Wellmann; Daniel Czarnowske (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
This paper quantifies the marginal willingness to pay for a reduction of automobile traffic. By using a new structural approach in a hedonic framework by Bishop and Timmins 2019 we are able to avoid common issues in hedonic studies using instrumental variables. Our analysis is based on data from nine large cities in Germany between 2016 and 2019 and includes 533,402 detailed observations at the apartment level as well as for various points of interest. To the best of our knowledge this is the first paper to conduct this analysis for Germany. We estimate that the average willingness to pay for a reduction of traffic by city and per year ranges between exteuro30.3-59.2 for a 10% reduction, exteuro93.8-158.3 for a 20% reduction and exteuro190.6-252 for a 30% reduction. The highest willingness to pay for a reduction of traffic is observed in Frankfurt am Main, the lowest in Leipzig. Further, we compute the expected gains for a reduction of traffic at the city level. In addition to the willingness to pay for a reduction of traffic, this considers the composition of the road network as well as for the number of households. Accordingly, these expected gains amount to exteuro163,970-1,019,454 exteuro for a 10% reduction, exteuro484,023-3,261,837 for a 20% reduction, and exteuro1,018,240-6,727,148 for a 30% reduction. The highest expected gains for a reduction of traffic is observed in Munich, the lowest in Leipzig
Keywords: O18; Q51; R48; 330; willingness to pay; traffic; air pollution; hedonic price models; rent prices; environmental policy